Room temperature polymerization of poly(3, 4‐ethylenedioxythiophene) as transparent counter electrodes for dye‐sensitized solar cells1. (22nd September 2014) - Gao, Suwen; Lan, Zhang; Wu, Wanxia; Que, Lanfang; Wu, Jihuai; Lin, Jianming
<x xml:space="preserve">Abstract</x> Poly(3, 4‐ethylenedioxythiophene) (PEDOT) counter electrode is prepared with in situ polymerization of 3, 4‐ethylenedioxythiophene on a fluorine‐doped tin oxide over‐layer glass at room temperature. The cyclic voltammetry, electrochemical impedance spectroscopy, and Tafel polarization are measured to evaluate the catalytic activity of PEDOT counter electrode for I3−/I− redox couple. Comparing the data with that of traditional thermal decomposed Pt counter electrode, it is found that PEDOT has higher catalytic activity than that of Pt counterpart. Power conversion efficiency of the dye‐sensitized solar cell (DSC) with PEDOT counter electrode can attain to 7.713%, a little higher than that of the cell with Pt counter electrode (7.300%). Taking the advantage of high transparency of PEDOT counter electrode, an Ag mirror is put on the back side of PEDOT counter electrode of the DSC to reflect light back for power conversion. Power conversion efficiency of the DSC with this special structure can be further enhanced to 8.359%, which mainly stems from the improved short‐circuit current density by the increased irradiated light intensity. Copyright © 2014 John Wiley & Sons, Ltd.